Pengaruh Digital Literacy, Financial Planning, dan Self-Control Terhadap Saving Behavior: Studi Kasus Generasi Z di Kota Pontianak - Alifa Tauris Miranda Bella; Giriati Giriati; Anwar Azazi; Wendy Wendy; Anggraini Syahputri (Lembaga Komunitas Informasi Teknologi Aceh (KITA), Indonesia, 2026)
The development of digital technology has led to changes in the financial behavior of Generation Z. However, these changes have not been fully accompanied by sound Saving Behavior. The phenomenon of low saving rates indicates that most individuals in Generation Z remain oriented toward short-term consumption rather than allocating income for savings. Therefore, digital literacy, financial planning, and Self-control are essential in fostering healthy Saving Behavior among Generation Z in Pontianak City. This study employs a causal quantitative approach, with data collected through questionnaires using purposive sampling techniques. The research sample consists of 200 Generation Z respondents in Pontianak City. Data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) with SmartPLS version 4 software. The results indicate that digital literacy has a positive but insignificant effect on Saving Behavior, while Financial Planning and Self-control have positive and significant effects on Saving Behavior.